2023
DOI: 10.1007/s10014-023-00469-2
|View full text |Cite
|
Sign up to set email alerts
|

Intraventricular central neurocytoma molecularly defined as extraventricular neurocytoma: a case representing the discrepancy between clinicopathological and molecular classifications

Daisuke Sato,
Hirokazu Takami,
Shunsaku Takayanagi
et al.

Abstract: Central neurocytoma (CN) is classically defined by its intraventricular location, neuronal/neurocytic differentiation, and histological resemblance to oligodendroglioma. Extraventricular neurocytoma (EVN) shares similar histological features with CN, while it distributes any site without contact with the ventricular system. CN and EVN have distinct methylation landscapes, and EVN has a signature fusion gene, FGFR1-TACC1. These characteristics distinguish between CN and EVN. A 30-year-old female underwent crani… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Additionally, 7/26 (27%) DNA‐methylation proven cases have no information concerning their precise location in the CNS [ 2 ]. Recently, Sato et al reported a left intraventricular tumour in a 30‐year‐old woman with histology suggestive of central neurocytoma (but the authors did not perform olig2 immunohitochemistry), FGFR1‐TACC1 fusion and a methylation score of 0.99 for the MC class of EVN [ 7 ]. This case and the current case 2 seem to suggest that a subset of tumours classified as MC EVN are not extraventricular.…”
mentioning
confidence: 99%
“…Additionally, 7/26 (27%) DNA‐methylation proven cases have no information concerning their precise location in the CNS [ 2 ]. Recently, Sato et al reported a left intraventricular tumour in a 30‐year‐old woman with histology suggestive of central neurocytoma (but the authors did not perform olig2 immunohitochemistry), FGFR1‐TACC1 fusion and a methylation score of 0.99 for the MC class of EVN [ 7 ]. This case and the current case 2 seem to suggest that a subset of tumours classified as MC EVN are not extraventricular.…”
mentioning
confidence: 99%